A useful guide of effective mesh-size decision in predicting the ultimate strength of flat- and curved plates in compression - Kim, D.K. (Shanghai Jiaotong University, 2022)
The present study aims to determine the appropriate size of mesh or the number of the element (NoE) for flat- and curved plates, which is suggested to assess its safety subjected to axial compression based on the ultimate limit state (ULS) design and analysis concept. The unstiffened panel (= plate) and stiffened panel, considered primary members of ships and ship-shaped offshore structures, are subjected to repeated axial compression and tension caused by continued vertical bending moments applied to the hull girder. Plates are attached with stiffeners by welding, and 6, 8 or 10 elements are generally recommended to allocate in flat-plate's breadth direction in between stiffeners for finite-element (FE) modelling, which enables the presentation of the shape of initial deflection applied to the plate. In the case of the load-shorting curve for curved plate, it is reported that the nonlinear behaviour characteristics, i.e., snap-through, snap-back, secondary buckling and others, appear in typical flank angle. To take this into account, we investigated the preferred number of elements (6, 8 or 10) generally applied to the flat plate whether it is an appropriate or more fine-sized element (or mesh) that should be considered. A useful guide is documented based on obtained outcomes which may help structural engineers select optimised mesh-size to predict ultimate strength and understand its characteristic of the flat and curved plates. Â© 2022